1997
DOI: 10.1086/304297
|View full text |Cite
|
Sign up to set email alerts
|

New Protostellar Collapse Candidates: An HCO+Survey of the Class 0 Sources

Abstract: We have observed 23 Class 0 sources in the HCO + J = 4 − 3 and 3 − 2 lines. The mean bolometric temperature of the 16 sources with well-determined values is 44 K and the mean luminosity is 5.7 L , excluding two sources of considerably higher luminosity. Nine sources, including three sources previously suggested to be collapsing, have the correct (blue) spectral line asymmetry for infall in both lines. Three sources have the opposite (red) asymmetry in both lines, and one source, L1157, has a red asymmetry in H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
186
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(194 citation statements)
references
References 72 publications
8
186
0
Order By: Relevance
“…Therefore, we use the expression "infall" signature with quotation marks in the rest of the article to remind the reader that the signature may not trace proper infall motions but only contraction motions when gravity does not (yet) dominate the dynamical evolution of these layers. The opposite signature, i.e., with the red peak emission of the self-absorbed transition stronger than the blue peak, has also been seen in other surveys of dense cores in the past (e.g., Gregersen et al 1997;Mardones et al 1997;Gregersen & Evans 2000. The red-skewed profiles are generally not very well understood.…”
Section: Contraction Motionsmentioning
confidence: 78%
“…Therefore, we use the expression "infall" signature with quotation marks in the rest of the article to remind the reader that the signature may not trace proper infall motions but only contraction motions when gravity does not (yet) dominate the dynamical evolution of these layers. The opposite signature, i.e., with the red peak emission of the self-absorbed transition stronger than the blue peak, has also been seen in other surveys of dense cores in the past (e.g., Gregersen et al 1997;Mardones et al 1997;Gregersen & Evans 2000. The red-skewed profiles are generally not very well understood.…”
Section: Contraction Motionsmentioning
confidence: 78%
“…The turbulent line width of this sample is highly supersonic. Our regions are at least 4 times more turbulent than regions involved in lower mass star formation (see Mardones et al 1997;Gregersen et al 1997). Based on comparison of power-law models using dust emission, Mueller et al (2002b) found that these cores were also about 100 times denser on average than the low-mass sample.…”
Section: Line Width-size Relationshipmentioning
confidence: 88%
“…Individual outflows in Serpens have been recorded in a wide variety of molecular tracers and different transitions; e.g. CS in Testi et al (2000), Mangum et al (1996), Wolf-Chase et al (1998); H 2 CO in Mangum et al (1996); CH 3 OH in Garay et al (2002) and Testi et al (2000); HCO + in Gregersen et al (1997) and Hogerheijde et al (1999); HCN, SO, and SiO in Hogerheijde et al (1999) and Garay et al (2002); NH 3 in Torrelles et al (1992). Widefield, homogenous outflow mapping of the Serpens Core has so far only been performed at the J = 1 → 0 (Narayanan et al 2002) and J = 2 → 1 (White et al 1995;Davis et al 1999) transitions of carbon monoxide.…”
Section: Introductionmentioning
confidence: 99%